Clinical value of diffusion-weighted MRI for differentiation between benign and malignant gallbladder disease: a systematic review and meta-analysis. (August 2021) - Kuipers, Hendrien; Hoogwater, Frederik JH; Holtman, Gea A; van der Hoorn, Anouk; de Boer, Marieke T; de Haas, Robbert J
Background: Radiological differentiation between benign and malignant gallbladder disease is important but remains challenging. Furthermore, the clinical value of diffusion-weighted imaging (DWI) remains unclear. Purpose: To determine the value of DWI in discriminating benign from malignant gallbladder disease by conducting a systematic review and meta-analysis. Material and Methods: The literature was systematically searched. Studies analyzing diagnostic value of DWI in gallbladder disease with histopathology or follow-up as reference standard were included. Study selection and data extraction were done by two reviewers independently. Methodological quality was assessed using the QUADAS-2 tool. Sensitivity and specificity were calculated and displayed in a forest plot. A sensitivity analysis was performed in case of outliers. Pooled sensitivity and specificity of DWI were plotted on a hierarchical summary receiver operating characteristic curve. If available, the added value of DWI to conventional magnetic resonance imaging (MRI) sequences was analyzed. Results: Out of 2456 articles, eight studies fulfilled the inclusion criteria; 592 patients with 221 malignant lesions were included. Pooled sensitivity and specificity rates were 0.87 and 0.84, respectively. In two studies, diagnostic accuracy rates improved after adding DWI to conventional MRI (64% and 75% for conventional MRI vs. 89% and 94% after combining conventional MRI with DWI). In another study, the area under the curve increased from 0.92 to 0.95. Conclusion: DWI appears to be an accurate imaging technique in discriminating benign from malignant gallbladder disease. To achieve optimal patient care, it should be part of multiparametric MRI and should be combined with other imaging modalities.